Bark Canker and Die-back of Dalbergia Sissoo in Haryana and Punjab Caused by Lasiodiplodia Theobromae - Chandra, Suresh; Prasad, R.; Harsh, N. S. K.; Ahuja, R.; Khatri, Shakuntala (Indian Forester, 2014)
Lasiodiplodia theobromae, a fungal pathogen causing stem cankers on Dalbergia sissoo is reported in Haryana and Punjab for the first time. It might have reached to D. sissoo from fruit trees like pear and peaches grown in the area where this fungus was reported earlier. The disease exhibited symptoms like dark spots on the bark with splitting, cankers and oozing of sap. The affected trees showed die back to varying degree. Bavistin was found as the most effective fungicide inhibiting complete growth of the fungus at 100 ppm among other fungicides. Among biological control agents Trichoderma harzianum exhibited distinct antagonism, T. koningii exhibited mycoparasitism, T. viride showed inhibition at the line of contact whereas Aspergillus niger showed overlapping. Spraying with Bavistin or Trucop on stem, branches and twigs of affected trees is recommended for checking the further spread of the disease. Chaubatia paste can also be applied while pruning the trees to check entry of the pathogen.